Susceptibility of Pigs to Zoonotic Hepatitis E Virus Genotype 3 Isolated from a Wild Boar. Issue 5 (31st July 2016) - Thiry, D.; Rose, N.; Mauroy, A.; Paboeuf, F.; Dams, L.; Roels, S.; Pavio, N.; Thiry, E.
Summary: In Europe, zoonotic hepatitis E virus (HEV) genotype 3 strains mainly circulate in humans, swine and wild boar. The aim of this study was to investigate the potential transmission of a wild boar originating HEV strain (WbHEV) to swine by intravenous or oral inoculation and to study the consequences of infection of a WbHEV strain, a WbHEV strain previously passaged in a pig and a swine HEV strain after oral inoculation. Firstly, an intravenous infection was performed for which five piglets were divided into two groups with three pigs inoculated with a WbHEV field strain and two pigs inoculated with a HEV‐negative swine liver homogenate. All pigs were necropsied 8, 9 and 10 days post‐inoculation. Secondly, an oral infection of 56 days was performed on 12 piglets divided into four groups inoculated with a WbHEV strain, a WbHEV strain previously passaged in swine, a swine HEV strain or a HEV‐negative swine liver homogenate. After intravenous inoculation, HEV RNA was detected in serum, bile, liver, spleen, duodenum, jejunum, colon, lung, gastro‐hepatic lymph nodes and faeces in all infected piglets. After oral inoculation, HEV RNA was detected in serum, bile, liver, gastro‐hepatic lymph nodes and faeces. Most of HEV‐inoculated pigs became seropositive at day 15. This study provides experimental evidence of early viral spread throughout the organism after intravenous infection with a WbHEV strain and supports the notion that such a zoonotic strain could be transmitted via the natural faecal–oral route of infection between wild boar and pigs but also between pigs.